Utilization of MOOC for Subak Values Extension: Maintaining Balinese Local Wisdom in Modern Education - Julianti, Rafika Tri; Sahiner, Mehmet; Khalid, Nurkaliza (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: To explore the use of Massive Open Online Courses (MOOC) as a medium for delivering Subak cultural values and to evaluate its effectiveness in increasing understanding, satisfaction, and relevance in the context of local wisdom preservation in digital education. Methodology: This study applied a mixed method with a sequential explanatory design. Quantitative data were collected through Likert-scale surveys from 15 MOOC participants. Qualitative data were obtained through in-depth interviews and literature review. Thematic analysis and descriptive statistics were used to analyze the data. Main Findings: Participants showed a high level of understanding of Subak values (mean score: 4.27) and were satisfied with the course delivery (mean score: 4.33). Interactive media such as videos and simulations supported better comprehension. Flexibility and accessibility were major strengths. Challenges include limited real-world interaction with Subak practices. Novelty/Originality of this study: This study is the first to evaluate the integration of Balinese Subak cultural values into a MOOC framework. It offers a new perspective on how digital platforms can effectively support the preservation of intangible cultural heritage through structured online learning accessible to a global audience.